New Media and the Effects of the Transformation of Arab Societies From Traditional to Virtual Relations: A Field Study on a Sample of Arab Communication Users in the UAE - Alti, Mustafa (The Arab Journal of Administration, 2020)
The research cares about studying the problem of new virtual relationships, which formed in the virtual environment, and affected social relations and family cohesion with negative effects, threatening the family entity of Arab society, and the sense of this problem came from negative phenomena resulting from the immersion of large numbers of users in the virtual environment of the new media, from Without preparation and prior awareness: which caused the emergence of hypothetical relationships between individuals, different from the social relations that are accepted and the acceptance of the human values ​​and meanings that express them. This led to the emergence of many negative phenomena, which amplified and spread very quickly to turn part of them into very complex and complex problems. It has become challenges facing family cohesion at the family and community levels. To study this problem and Topics the resulting effects, a descriptive approach was used to describe the problem and survey a sample from the research Society, and the analytical approach was used to analyze field study data and extract the results that answer the research questions and achieve its goals, and one of the most prominent results of the research was that 57.3% Of the respondents believe that the communication sites have damaged all their social relationships, compared to 23.6% see it as damaging the relationship of the respondents with family and relatives, compared to 19% believe that it has damaged the relationship of the respondents with friends and co-workers. The results indicated that 44% believed that the communication sites caused the dissolution of family ties, compared to 22.6% who believed that they contributed to the development of their social life, and 14.3% of the sample believed that it could help in strengthening family ties, and 11% of the respondents believed that they had affects Others, while 8% believed that it caused social development. The results of the research confirmed that 20% of the respondents establish hypothetical relationships to satisfy missing social needs of the family and relatives, 12.3% evaluate these relationships to satisfy missing needs among friends, and 16.6% establish these relationships to satisfy emotional needs, compared to 8.3% to satisfy missing needs when Co-workers, and there were 42.6% were assessing these relationships for other reasons. It was clear from the results that 59.3% of the respondents do not believe that the hypothetical relationships they establish on the communication sites can be a suitable alternative to their social relationships, while 32% of the respondents believe, on average, that the hypothetical relationships can be an alternative to their social relations, compared to 8.6% They largely believed that hypothetical relationships were a suitable alternative to their social relationships. The research reached a number of recommendations that call for intensifying studies and converting their results into plans and programs to find appropriate solutions to confront the negative effects resulting from this problem.